Energy-efficient resource allocation algorithm for massive MIMO OFDMA downlink system - Ying HU; Bao-feng JI; Yong-ming HUANG; Fei YU; Lv-xi YANG (Tongxin xuebao)
An algorithm is proposed for energy-efficient resource allocation scheme in massive MIMO OFDMA downlink mobile communication system.A mathematical formulation of optimization issue is provided with the objective of maximizing system energy efficiency lower bound under the minimum data rate requirement of user,meanwhile the BS uses a zero-forcing(ZF) precoding.And then for optimizing energy efficiency function,the bandwidth allocation,power allocation and the number of antenna arrays at the BS are adjusted synchronously.First,an iterative algorithm derived from optimality condition for bandwidth assignment is proposed.Second,the properties of fractional programming and convex optimization are used to maximize the energy efficiency.Specifically,both the number of antenna arrays at the BS and the transmit data rate at the user are adjusted.Simulation results show that the proposed schemes not only have less iteration number but also have good perform for system energy efficiency and throughput.